Caxambu do Horizonte a Andorinha : memória e pertencimento da cultura negra - Mardgan, Jacyara Conceição Rosa (2017)
The research that follows, aims to analyze the processes of belonging and memory in the construction of the cultural practice of Afro-Brazilian tradition caxambu, which is planted by the state of Espírito Santo and leaves its mark in the southern region o